Fractional-Order System: Control Theory and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
International experts contribute to Fractional- and Integer-Order System: Control Theory and Applications, providing an authoritative overview of the most recent developments in control theory as well as practical examples of fractional- and integer-order systems. Generously referenced and illustrated, the reprint highlights the growing interest in control science and is an invaluable resource for applied and industrial mathematicians, biological, control, electrical and electronics engineers and scientists.